Combining top-down and bottom-up change management strategies in implementation of ACP: the My Wishes program in South West Sydney, Australia. Issue 1 (1st June 2011) - Shanley, C; Johnston, L; Walker, A
Abstract : Attempts to introduce advance care planning (ACP) and make it a part of normal clinical practice present significant challenges and one way of approaching these is to utilise the change management literature. One aspect of this literature is the relative importance of top-down and bottom-up strategies to promote and support organisational change. The Sydney South West Area Health Service (SSWAHS) launched the My Wishes Advance Care Planning program in early 2010 and the implementation plan employed both top-down and bottom-up strategies. Key strategies of a top-down nature included: a comprehensive, organisational-wide policy; several new forms as part of the medical records of all hospitals; incorporation of these into the developing electronic medical records system; hospital General Managers having to report on local implementation of the program; involvement of local General Practice Divisions as program partners; and launch of a comprehensive website (http://www.mywishes.org.au ). Bottom-up strategies included: community information forums; workshops for health service and residential care staff; liaising with hospital departments and other services to include ACP information on their normal education agenda; putting ACP on the agendas of other initiatives in the health service such as chronic care and end-of life care; and supporting staff who would be advocates for the program.